ps05_soln

ps05_soln - 18.03 PS5 Solutions—Spring 09 1a(first...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 18.03 PS5 Solutions—Spring 09 1a. (first solution) Given mx 00 + kx = 0, the characteristic polynomial p ( r ) = mr 2 + k has roots r = ± ( p k/m ) i . Let ω = p k/m . Then z = ce iωt is a complex-valued solution for any constant c ∈ C . The real part has the form x = A cos( ω n t- φ ) with ω n = ω = p k/m Indeed, write c = Ae iθ , so that z = Ae i ( ωt + θ ) is a complex-valued solution, and x = Re z = A cos( ωt + θ ) is a real-valued solution. This is equivalent to x = A cos( ωt- φ ) and φ =- θ . Starting with the other complex-valued solution, z = ce- iωt , yields the same family of real solutions. 1a. (second solution) We start by seeing under what conditions x = A cos( ωt- φ ) is a solution to the ODE mx 00 + kx = 0: mx 00 + kx =- mAω 2 cos( ωt- φ ) + kA cos( ωt- φ ) = A cos( ωt- φ )(- mω 2 + k ) which is zero exactly when ω = ± p k/m . Since frequency is positive by convention, ω = ω n = p k/m . To see that every solution is of the form x = A cos( ω n t- φ ) with ω n = p k/m , one should check that the form is flexible enough to support all possible val- ues of x (0) and x (0). This leads to two simultaneous equations for the two parameters A and φ . But students are not required to carry this out to confirm that there is always a solution. The fact that there are no other solutions follows from the fact that a solution is uniquely specified by the initial conditions x (0) and x (0). 1b. The initial conditions x (0) = x , x (0) = 0 for x = A cos( ω n t- φ ). lead to A cos φ = x ω n A sin φ = 0 which means that φ = 0 and A = x , so x = x cos( ω n t ). The first time that x = 0, we have ω n t = π/ 2. In general, x =- ω n x sin( ω n t ), so at the time when ω n t = π/ 2, then x =- ω n x . The kinetic energy is (1 / 2) m ( x ) 2 = (1 / 2) mω 2 n x 2 = (1 / 2) m ( k/m ) x 2 = (1 / 2) kx 2 . 1c. Given E = (1 / 2) m ( x ) 2 + (1 / 2) kx 2 , we have E = mx x 00 + kxx = x ( mx 00 + kx ) = 0....
View Full Document

This note was uploaded on 05/06/2010 for the course 18 18.03 taught by Professor Unknown during the Spring '09 term at MIT.

Page1 / 4

ps05_soln - 18.03 PS5 Solutions—Spring 09 1a(first...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online